From inflammation to cutaneous repair: Topical application of lupeol improves skin wound healing in rats by modulating the cytokine levels, NF-κB, Ki-67, growth factor expression, and distribution of collagen fibers - Beserra, Fernando Pereira [UNESP] (2020)
Skin wound healing is a highly complex event that involves different mediators at the cellular and molecular level. Lupeol has been reported to possess different biological activities, such as anti-inflammatory, antioxidant, antidiabetic, and in vitro wound healing properties, which motivated us to proceed with in vivo studies. We aimed to investigate the wound healing effect of lupeol-based cream for 3, 7, and 14 days. Wound excisions were induced on the thoraco-lumbar region of rats and topically treated immediately after injury induction. Macroscopic, histopathological, and immunohistochemical analyses were performed. Cytokine levels were measured by ELISA and gene expression was evaluated by real-time RT-qPCR. Our results showed a strong wound-healing effect of lupeol-based cream after 7 and 14 days. Lupeol treatment caused a reduction in proinflammatory cytokines (TNF-a, IL-1β, and IL-6) and gene and protein NF-κB expression, and positively altered IL-10 levels, showing anti-inflammatory effects in the three treatment periods. Lupeol treatment showed involvement in the proliferative phase by stimulating the formation of new blood vessels, increasing the immunostaining of Ki-67 and gene expression, and immunolabeling of vascular endothelial growth factor (VEGF) and epidermal growth factor (EGF), and increasing gene expression of transforming growth factor beta-1 (TGF-β1) after seven days of treatment. Lupeol was also involved in the tissue regeneration phase by increasing the synthesis of collagen fibers noted in the three treatment periods analyzed. Our findings suggest that lupeol may serve as a novel therapeutic option to treat cutaneous wounds by regulating mechanisms involved in the inflammatory, proliferative, and tissue-remodeling phases.